2018
DOI: 10.1177/0971890718758199
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotyping of Leadership

Abstract: This study attempts to understand organizational commitment (OC) in relation to transformational leadership (TL) behaviours. It also tries to understand whether gender of the leader acts as a moderating variable in relation to TL and OC. It gives critical insights on gender stereotyping of leadership in public sector banks (PSBs) taking theoretical inputs from role congruity theory. A survey based on validated statements was used to collect data from 328 employees of PSBs working in the branches. Correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Economists consider the banking sector as the backbone of any economy; in the Indian context, also banking sector mobilises the savings of households to the industrial and other sectors, hence ensuring the smooth functioning of the economy. Yadav and Yadav (2018) highlighted branch managers’ critical role in achieving the efficiency and effectiveness of branches by implementing the strategy, plan, or action of top management and handling motivation and other human resource issues. As per the Gopalakrishna’s (2014) committee’s report on capacity building in banks and non-banks, the branch manager’s leadership skills are among the most critical skills through which the manager assures the effective and efficient functioning of the branch.…”
Section: Methodsmentioning
confidence: 99%
“…Economists consider the banking sector as the backbone of any economy; in the Indian context, also banking sector mobilises the savings of households to the industrial and other sectors, hence ensuring the smooth functioning of the economy. Yadav and Yadav (2018) highlighted branch managers’ critical role in achieving the efficiency and effectiveness of branches by implementing the strategy, plan, or action of top management and handling motivation and other human resource issues. As per the Gopalakrishna’s (2014) committee’s report on capacity building in banks and non-banks, the branch manager’s leadership skills are among the most critical skills through which the manager assures the effective and efficient functioning of the branch.…”
Section: Methodsmentioning
confidence: 99%
“…Some recent works have examined the role of transformational leadership in a public organization in India. Yadav and Yadav (2018) examined organizational commitment in public banks and observed that transformational leadership was related to stronger organizational commitment.…”
Section: Transformational Leadership and Institutional Entrepreneursh...mentioning
confidence: 99%
“…These abilities can also encourage innovative behaviour for the reason that these qualities are closely related to the transformational leadership style (Eagly & Carli, 2003;Shaw et al, 2011). These limitations highlight the gaps in the theme of women's representation in public sector that needs to be filled by future research (Koburtay et al, 2019;Yadav & Yadav, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study aims to fill the gap on the theme of gender and PSL, particularly by focusing on investigating the critical factors influencing women's representation at the top management level in public sector organizations in non-western contexts, as recommended by previous studies (Koburtay et al, 2019;Yadav & Yadav, 2018). To fill this research gap, this study will be conducted in Indonesia as a lowmiddle income country in Southeast Asian Region, with the East Nusa Tenggara (ENT) Provincial Government as the study site (World Bank, 2022).…”
Section: Introductionmentioning
confidence: 99%